Variable gain switching exact differential observer‐based compensation control for servo system with backlash. Issue 14 (8th July 2021) - Sun, Guofa; Xu, Yaming; Wang, Yan; Wang, Gang
Abstract: This paper proposes a novel variable gain switching exact differential observer (SEDO) to deal with the state estimation of mechanical servo system with unknown backlash. In order to compensate unknown non‐linear backlash accurately, a switching backlash torque mathematic model is constructed to describe the input–output relationships of backlash. Then, based on the switching backlash torque mathematic model, a novel SEDO with variable gain strategy is implemented to compensate the influence of backlash and estimate system states accurately in terms of the change of real operation conditions. Moreover, the designed controller further alleviates the computational burden by conducting a feedforward compensation strategy, part of which is shared by the observer. It is proven that all the signals in the closed‐loop system are bounded, observation error and tracking error are convergent to a small compact set of the origin. Two simulations and two different motor servo test rigs are established to further illustrate the effectiveness of the proposed approach.